2023
DOI: 10.1161/hypertensionaha.122.20588
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Hypertension: Epigenetic Mechanism Involved in Development of Salt-Sensitive Hypertension

Abstract: This review highlights recent insights into the epigenetic mechanism of salt-sensitive hypertension from the fetus to the elderly population, mainly focusing on the DNA methylation and histone modification-mediated regulation of hypertension-associated genes. Maternal malnutrition during pregnancy induces upregulation of angiotensin receptor 1a ( AT1a ) by aberrant DNA methylation, and increased AT1A activity in the hypothalamus develops prenatally programmed salt-sensitive hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…MR‐related hypertension has recently been proposed to be associated with upregulation of Wnt5a‐RhoA/ROCK‐MYPT1 signaling in vascular smooth muscle cells. 18 , 19 However, whether this signaling represents the mechanism mediating cardiac hypertrophy and fibrosis remains unknown. We discovered upregulation of MYPT2 and MLCP activity in cardiomyocytes both in vivo and in vitro after treatment with aldosterone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR‐related hypertension has recently been proposed to be associated with upregulation of Wnt5a‐RhoA/ROCK‐MYPT1 signaling in vascular smooth muscle cells. 18 , 19 However, whether this signaling represents the mechanism mediating cardiac hypertrophy and fibrosis remains unknown. We discovered upregulation of MYPT2 and MLCP activity in cardiomyocytes both in vivo and in vitro after treatment with aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…MR‐related hypertension has recently been reported to be associated with the upregulation of ROCK (RhoA/Rho kinase)‐myosin phosphatase target subunit 1 (MYPT1) signaling in arteries. 18 , 19 However, how MYPT signaling affects the heart in MR‐related hypertension remains unknown. A recent study demonstrated that cardiac MLCP plays an important role in cardiac fibrosis as a target of ROCK.…”
mentioning
confidence: 99%
“…Epigenetics, which explores the dynamic interplay between genetic factors and the environment, emerges as a critical player in the regulation of blood pressure. Epigenetic changes can be influenced by environmental stimuli such as nutrition, aging, and pharmaceuticals, and importantly, these changes possess the potential for reversibility ( 8 , 9 ). This characteristic sets the stage for a spectrum of treatment possibilities distinct from those for genetic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of the risk for hypertension is inherited 5 and these influences are epigenetically modified by intrauterine and life events. 8,9 Numerous reviews have focused on the critical role of endothelial dysfunction, however, VSMCs also suffer chronic injury. 10 Multiple proinflammatory signaling pathways are hyperactivated including TNF-α (tumor necrosis factor alpha), 11 IL (interleukin)-1β, 12 Ang II (angiotensin II), 13 and growth factors, 14 supporting an inflammatory response that correlates with disease severity.…”
mentioning
confidence: 99%